Body image and its relationship with exercise and sports in Turkish lower-limb amputees who use prosthesis - TATAR, YAŞAR (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2010)
Purpose. - In this study, we investigated whether Turkish lower-limb amputees (LLA) using prosthesis, who participate in sports and exercise activities, have a different body image from those who do not participate in such physical activities. Method. - For this evaluation, we used the Amputee Body Image Scale (ABIS); in addition, a questionnaire for assessment of demographic characteristics of the subjects and issues regarding use of the prosthesis was applied. The study was conducted on 17 Turkish LLA participating in sports and exercise, and on 20 Turkish LLA not participating in sports and exercise activities. Results. - The mean ABIS score of LLA participating in sports and exercise was 25,5 +/- 7,33; mean ABIS score of LLA not participating in sports and exercise was 35,94 +/- 12,24; this difference was statistically significant (Mann-Whitney U, p < 0.05). ABIS scores for men and women were similar, regardless of participation in exercise and sports. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: ABIS; Amputation psychology; Limb loss; WHEELCHAIR SPORT; AMPUTATION; SATISFACTION; DEPRESSION; PEOPLE